2010
DOI: 10.1016/j.physleta.2009.12.077
|View full text |Cite
|
Sign up to set email alerts
|

DNA breathing dynamics in the presence of a terahertz field

Abstract: We consider the influence of a terahertz field on the breathing dynamics of double-stranded DNA. We model the spontaneous formation of spatially localized openings of a damped and driven DNA chain, and find that linear instabilities lead to dynamic dimerization, while true local strand separations require a threshold amplitude mechanism. Based on our results we argue that a specific terahertz radiation exposure may significantly affect the natural dynamics of DNA, and thereby influence intricate molecular proc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
110
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(117 citation statements)
references
References 18 publications
(13 reference statements)
3
110
0
4
Order By: Relevance
“…In addition to conventional thermal effects, however, several researchers have proposed that THz radiation may also induce low-level thermal, nonthermal, or more appropriately, microthermal effects. These theories were initially hypothesized by Frohlich et al in 1971 [99, 100], and more recent studies propose that these microthermal effects are mediated through the direct coherent excitation of biomolecules [99] or linear/nonlinear resonance mechanisms [101,102].…”
Section: Thermal Effects On Biological Macromoleculesmentioning
confidence: 99%
“…In addition to conventional thermal effects, however, several researchers have proposed that THz radiation may also induce low-level thermal, nonthermal, or more appropriately, microthermal effects. These theories were initially hypothesized by Frohlich et al in 1971 [99, 100], and more recent studies propose that these microthermal effects are mediated through the direct coherent excitation of biomolecules [99] or linear/nonlinear resonance mechanisms [101,102].…”
Section: Thermal Effects On Biological Macromoleculesmentioning
confidence: 99%
“…However recent research by Alexaandrov et al [30] has indicated that under certain conditions (high power, long exposure time and the right frequency) the THz field might be able unzip double-stranded DNA, creating bubbles in the double strand that could significantly interfere with processes such as gene expression and DNA replication. Note that these results are all numerical and have not yet been experimentally verified.…”
Section: Application To the Human Bodymentioning
confidence: 99%
“…Отметим, что исследование динамики ДНК, находящейся под внешним воздействием, представляет самостоятельный интерес, в частности, стимулированный быстрым развитием терагерцовых технологий [28], однако в рамках настоящей работе мы ограничиваемся лишь демонстрацией принципиальных возможностей такого способа возбуждения молекулы ДНК.…”
Section: нелинейные колебания и волны в днк возбуждаемые внешним возunclassified